Intrinsically Stretchable Organic Solar Cells beyond 10% Power Conversion Efficiency Enabled by Transfer Printing Method. (23rd June 2021) - Wang, Zhenye; Xu, Meichen; Li, Zhilin; Gao, Yerun; Yang, Lvpeng; Zhang, Di; Shao, Ming
Abstract: Stretchable organic solar cells (OSCs) simultaneously possessing high‐efficiency and robust mechanical properties are ideal power generators for the emerging wearable and portable electronics. Herein, after incorporating a low amount of trimethylsiloxy terminated polydimethylsiloxane (PDMS) additive, the intrinsic stretchability of PTB7‐Th:IEICO‐4F bulk heterojunction (BHJ) film is greatly improved from 5% to 20% strain without sacrificing the photovoltaic performance. The intimate multi‐layers stacking of OSCs is also realized with the transfer printing method assisted by electrical adhesive "glue" D‐Sorbitol. The resultant devices with 84% electrode transmittance exhibit a remarkable power conversion efficiency (PCE) of 10.1%, which is among the highest efficiency for intrinsically stretchable OSCs to date. The stretchable OSCs also demonstrate the ultra‐flexibility, stretchability, and mechanical robustness, which keep the PCE almost unchanged at small bending radium of 2 mm for 300 times bending cycles and retain 86.7% PCE under tensile strain as large as 20% for the devices with 70% electrode transmittance. The results provide a universal method to fabricate highly efficient intrinsically stretchable OSCs. Abstract : An intrinsically stretchable organic solar cell (OSC) with an efficiency of over 10% is achieved by the transfer printing method. The ductility of bulk heterojunction film is greatly improved to 20% by introducing polydimethylsiloxane additives, and intimated multilayer stacking is realized with the assistance of electrical adhesive D‐Sorbitol. The stretchable OSC exhibits ultra‐flexibility and superior stretchability without sacrificing the device performance.